2017
DOI: 10.4172/2155-9872.1000352
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Methodology for the Quantification of B-Vitamers in Breast Milk

Abstract: With this report we present the development, validation and application of an analytical methodology for the quantification of 18 water soluble vitamers and secreted or biological forms in breast milk. On a relatively low amount of breast milk (200 µL), we applied isotope dilution-based sample preparation based on a combination of enzymatic treatment and protein precipitation using acidic methanol enriched with stable isotope labelled internal standards. Compounds separation was achieved by reversed-phase liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…First, we only used 5-MeTHF as an internal standard, whereas one cannot exclude that other bioactive forms exist in breast milk, such as folic acid found in supplemented food. Indeed, results with LC-MS/MS suggest that this form could be present in significant amounts in breast milk [10]. Moreover, we were unable to identify the reason for and nature of an unexpected small increase in folate signal when undiluted samples were heated to denature FBP.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…First, we only used 5-MeTHF as an internal standard, whereas one cannot exclude that other bioactive forms exist in breast milk, such as folic acid found in supplemented food. Indeed, results with LC-MS/MS suggest that this form could be present in significant amounts in breast milk [10]. Moreover, we were unable to identify the reason for and nature of an unexpected small increase in folate signal when undiluted samples were heated to denature FBP.…”
Section: Discussionmentioning
confidence: 83%
“…A previous report suggested that microbiological assays might lead to measurement of overestimated folate levels in breast milk [11]. We thus chose instead to compare the presented method with an LC-MS/MS method recently developed in house [10]. It is important to notice that this methodology detects and quantifies two major folate forms with vitamin B 9 activity, namely 5-MeTHF and folic acid.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations